Competência interprofissional para a gestão do cuidado às condições crônicas na atenção primária à saúde: uma revisão sistemática. - Silva, Elainy Cristiny Ponte (2022)
With the current health situation in the country and the epidemiological transitions, especially regarding chronic conditions, the need for change in health policies and in the management of political resources to transform the organizational structure of the public health system is evident. In this perspective, it is necessary that the health systems resignify themselves in order to guarantee the integral attention to the health of the users, in view of the demographic and epidemiological transitions and the incorporation of new technologies. This study aims to build a Profile of Interprofessional Competencies for the management of care for chronic conditions within the scope of Primary Health Care, based on a Systematic Review (SR). This is a descriptive exploratory study, under a qualitative approach in secondary sources, using the Systematic Review method. For the design of this SR with metasynthesis, the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method were adopted. The evaluation of the eligibility of the studies was carried out by two reviewers, independently, guided by inclusion and exclusion criteria. Searches were performed in the following databases: Medline/Pubmed; Web Of Science; Cinahl; Scopus; Cochrane Library; Virtual Health Library (BVs); Scielo; Psycinfo; Eric; Google Scholar and descriptors available in DeCS and MeSH were used, as well as keywords and Boolean operators 'and' and 'or' , with the aid of truncating methods. Included were: primary studies, available free of charge or by photocopy purchase, publications in any language and year, and gray literature. After searching these databases, all results were imported into the free software Rayyan Systems Inc. The selected studies were submitted to a quality investigation using the checklist proposed by the Critical Appraisal Skills Program (CASP) for the evaluation of qualitative studies. The qualitative meta-synthesis of the studies was carried out with the support of the NVivo Pro 11 software - educational license with OSB Software - number 2015877. From the construction of this systematic review, it was possible to analyze 115 studies, of which 102 articles and 13 documents from the gray literature. It was found that descriptive exploratory studies prevailed among those included, the predominant countries were Canada, Brazil, United States, United Kingdom and Australia, the dominant areas of knowledge were Nursing and Medicine and the years of publications that had relevant quantitative were 2021, 2017 and 2016. In the qualitative analysis of the studies, it was possible to observe and separate the initial categories present in the articles and documents included and that are directly related to the interprofessional competences for the management of care for chronic conditions, into three major classes, which are: Interprofessional approach to the subject , the family and the territory; Interprofessional collaborative strategies and practices and Interprofessional collaboration in the care and protection network. And so it was possible to discuss the categories related to the theme of each of these classes and reflect on the necessary skills in the professional performance for the management of care for chronic conditions in primary care. Therefore, this study made it possible to observe, in addition to the profile of the included studies, the main initial categories that are considered as interprofessional competences for the management of the care of chronic conditions in primary care, as well as to discuss with the literature the importance of these findings for the attention to the conditions chronicles.